IMPLEMANTASI PENGAWASAN OTORITAS JASA KEUANGAN TERHADAP LEMBAGA KEUANGAN MIKRO (Studi Kasus Pada Bank Perkreditan Rakyat Yang Terdaftar Dan Diawasi OJK Regional 8 Bali Dan Nusa Tenggara) - Ni Putu Galuh Nirmalasari; Ni Wayan Suartini; I Nyoman Gede Supraptha (Nusantara Hasana Journal, 2022)
The Financial Services Authority is an independent institution and is free from interference from other parties that has the functions, duties, authorities as regulation, supervision and protection. One of the institutions that is closely monitored by the Financial Services Authority is the Microfinance Institution. The Financial Services Authority also stipulates that if the business activities of a Microfinance Institution exceed one district/city area, the institution must transform into a Rural Bank or Sharia Rural Financing Bank. This policy is of course related to the many problems in the banking sector that occurred in the crisis and impacted the 21 national private banks which were liquidated by Bank Indonesia, which found various irregularities so that many questioned Bank Indonesia's supervision. This study aims to describe the supervision of the Financial Services Authority and the Standard Operating Procedures of the Financial Services Authority on the performance of Microfinance Institutions. Data collection techniques were carried out by questionnaires and literature studies, with quantitative descriptive analysis techniques. The results of the study show: (1) The supervision of the Financial Services Authority partially has a positive and significant influence on the performance of Microfinance Institutions, it can be said that the significance value is 0.000 with a coefficient value of 0.429. (2) Standard Operating Procedures of the Financial Services Authority partially have a positive and significant effect on the performance of Microfinance Institutions, it can be said that the significance value is 0.000 with a coefficient value of 0.661. (3) Supervision of the Financial Services Authority and Standard Operating Procedures of the Financial Services Authority simultaneously have a positive and significant influence on the performance of Microfinance Institutions, it can be said that this is because a significance value of 0.000 is obtained.